SCREENING OF LDPE PLASTIC-WASTE-DEGRADING BACTERIA USING WINOGRADSKY COLUMN - Bowo Sugiharto; Alifia Harisma Rustanti (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2026)
This study aims to screen Low-Density Polyethylene (LDPE)-degrading bacteria from three highly plastic-contaminated environments: the Jatimalang River stream, Bekonang Market soil, and Joho Village Waste Disposal Site. The research used the Winogradsky column method with two incubation periods: 1 month and 2 months. This research was conducted with 3 repetitions using a descriptive-quantitative data analysis approach, and was a preliminary screening. Observed parameters included the percentage of plastic degradation, biofilm thickness, physical changes in LDPE, and bacterial morphology isolated using Nutrient Agar. The results showed that the highest degradation occurred in the waste-disposal soil (TPS), with values of 34.37% (1 month) and 40.62% (2 months), followed by river soil (22.72% and 27.27%) and market soil (13.63% and 18.18%). Biofilm thickness was also most significant in TPS samples, reaching 0.57 ± 0.01 and 0.91 ± 0.03 μm. Physical changes included yellowish to brownish discoloration, increased roughness, and enhanced elasticity of LDPE. All bacterial isolates exhibited irregular colony forms, lobate margins, flat elevations, and cream-to-yellow pigmentation. Gram staining identified all isolates as Gram-positive bacteria. These findings indicate that plastic-contaminated environments hold strong potential as natural sources of LDPE-degrading bacteria.